Corynebacterium bouchesdurhonense sp. nov., and Corynebacterium provencense sp. nov., two new species isolated from obese patients. (September 2019) - Lo, C.I.; Niang, E.H.A.; Ndongo, S.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Corynebacterium bouchesdurhonense sp. nov. strain Marseille-P2067 T (= CSURP2067; = DSM100846) and Corynebacterium provencense sp. nov. strain Marseille-P2161 T (= CSURP2161; = DSM101074) are two new species from the order Corynebacteriales that were isolated from obese French individuals.